2022
DOI: 10.1002/cphc.202200392
|View full text |Cite
|
Sign up to set email alerts
|

Coherence and Efficient Energy Transfer in Molecular Wires: Insights from Surface Hopping Simulations

Abstract: Understanding the dynamics of electronic energy transfer through a molecular wire is essential to understand the working of natural processes like photosynthesis. We investigate simpler 2 and 3‐site model Hamiltonians in this work to understand the importance of coherence to efficient energy transfer. We compare the results of surface hopping simulation with that of numerically exact results and rate theories. Different parameters are analyzed, motivated by a photosynthetic molecular wire – the FMO complex. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…It is this anomalous pronounced dependence of the population dynamics on some values of the perturbative coupling between sites 1 and 3 which has been noticed in ref . We have managed to derive simple analytical expressions for the population dynamics of the 3-site system which explains this anomalous behavior and provide a range for the variation in time scales of the dynamics.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…It is this anomalous pronounced dependence of the population dynamics on some values of the perturbative coupling between sites 1 and 3 which has been noticed in ref . We have managed to derive simple analytical expressions for the population dynamics of the 3-site system which explains this anomalous behavior and provide a range for the variation in time scales of the dynamics.…”
Section: Resultsmentioning
confidence: 90%
“…A recent numerical study has reported an unusually high variation in the uphill dynamics following a minor change in the intersite coupling between site-1 and site-3. 15 The authors attempted to explain this behavior by considering variances in the crossings of diabatic electronic potential energy surfaces corresponding to each site. However, a comprehensive quantitative description of this anomalous behavior is missing, and this will be the main motivation for our work.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation